Optimal Growth and Continual Planning Revision - Goldman, S. M. (Review of Economic Studies, 1968)
Journal Article Optimal Growth and Continual Planning Revision Get access S. M. Goldman S. M. Goldman University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 2, April 1968, Pages 145–154, https://doi.org/10.2307/2296544 Published: 01 April 1968